Longitudinal assessment of established risk stratification models in patients with monoclonal gammopathy of undetermined significance - Zuern, Kosima; Hielscher, Thomas; Werly, Annika; Breitkreutz, Iris; Sauer, Sandra; Raab, Marc-Steffen; Müller-Tidow, Carsten; Goldschmidt, Hartmut; Mai, Elias K. (Blood cancer journal, 2024)
Risk of progression of monoclonal gammopathy of undetermined significance (MGUS) into multiple myeloma and related plasma cell disorders can be determined by three major risk stratification models, namely Mayo2005, Sweden2014, and NCI2019. This retrospective study of 427 patients with MGUS diagnosed according to the 2014 International Myeloma Working Group criteria aimed to describe and analyze the longitudinal applicability of these risk models. In all three models, the majority of patients remained at their baseline risk group, whereas small numbers of patients migrated to a different risk group. Proportions of patients among risk groups remained stable over time (e.g. Mayo2005 model, low-risk group, at baseline: 43%, after 1, 2, 3, 4, 5, and 8 years: 40%, 37%, 37%, 43%, 44%, and 43%). All three risk models reliably distinguished risk of progression at baseline, upon yearly reassessment (e.g. 1 year from diagnosis) and in time-dependent analyses. Upstaging to a high-risk category was associated with an increased risk of progression in all three models (Mayo2005: hazard ratio [HR] = 5.43, 95% confidence interval [95% CI] 1.21-24.39, p = 0.027; Sweden2014: HR = 13.02, 95% CI 5.25-32.28, p < 0.001; NCI2019: HR = 5.85, 95% CI 2.49-13.74, p < 0.001). Our study shows that MGUS risk stratification models can be applied longitudinally to repeatedly determine and improve individual risk of progression. Patient migration to higher risk categories during follow up should prompt more frequent monitoring in clinical routine.